First-in-Human Experience With Ultra-Low Temperature Cryoablation for Monomorphic Ventricular Tachycardia - De Potter, Tom; Balt, Jippe C; Boersma, Lucas; Sacher, Frederic; Neuzil, Peter; Reddy, Vivek; Grigorov, Ilya; Verma, Atul (JACC. Clinical electrophysiology, 2023)
Ultra-low temperature cryoablation (ULTC) using near-critical nitrogen (-196oC) has been shown to produce durable, contiguous, transmural lesions in ventricles of animal models. This report summarizes acute experience with ULTC in the first-ever 13 patients with recurrent monomorphic ventricular tachycardias (VTs) of both ischemic cardiomyopathy and nonischemic etiologies enrolled in the CryoCure-VT (Cryoablation for Monomorphic Ventricular Tachycardia; NCT04893317) clinical trial. After an average of 9.6 ± 4.6 endocardial ULTC lesions per patient, no clinical ventricular tachycardias were inducible in 91% of patients. Two procedure-related serious adverse events recorded in 2 patients resolved post-procedurally without clinical sequelae. Further investigation of both acute and chronic outcomes is warranted and ongoing.
Keywords: Animals; Endocardium; Temperature; lidé; Heart Ventricles; kryochirurgie; zvířata; endokard; Cryosurgery; teplota; Tachycardia, Ventricular; komorová tachykardie; srdeční komory; Humans